Assessment of transmissibility and measures effectiveness of SARS in 8 regions, China, 2002-2003 - Rui, Jia; Qu, Huimin; Zhang, Shuo; Liu, Hong; Wei, Hongjie; Abudunaibi, Buasiyamu; Li, Kangguo; Zhao, Yunkang; Liu, Qiao; Fang, Kang; Gavotte, Laurent; Frutos, Roger; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Severe acute respiratory syndrome (SARS) is a form of atypical pneumonia which took hundreds of lives when it swept the world two decades ago.The pathogen of SARS was identified as SARS-coronavirus (SARS-CoV) and it was mainly transmitted in China during the SARS epidemic in 2002-2003. SARS-CoV and SARS-CoV-2 have emerged from the SARS metapopulation of viruses. However, they gave rise to two different disease dynamics, a limited epidemic, and an uncontrolled pandemic, respectively. The characteristics of its spread in China are particularly noteworthy. In this paper, the unique characteristics of time, space, population distribution and transmissibility of SARS for the epidemic were discussed in detail.Methods We adopted sliding average method to process the number of reported cases per day. An SEIAR transmission dynamics model, which was the first to take asymptomatic group into consideration and applied indicators of R0, Reff, Rt to evaluate the transmissibility of SARS, and further illustrated the control effectiveness of interventions for SARS in 8 Chinese cities.The R0 for SARS in descending order was: Tianjin city (R0= 8.249), Inner